PENINGKATAN PEMAHAMAN MATERI BANGUN DATAR MELALUI MODEL MAKE A MATCH PADA MATA PELAJARAN MATEMATIKA SISWA KELAS IV DI SDN BANAR JAYA - Neng Seli Setiani (INSTRUKTUR, 2022)
The understanding of class IV SDN BANAR JAYA, especially mathematics lessons, is slightly lacking, the purpose of holding this study is to find out the ability of grade IV students to build flat material using make a match technique. The method used is Class Action Research (PTK) through planning, implementing, observing, and reflecting. The value of student learning outcomes before the improvement was carried out showed below the KKM, which was 14%. After carrying out the improvement of cycle I there is an increase with the number of average values of 68%, when compared from the previous cycle, cycle II produces a very high increase. The result of cycle II is an average value of 93%. With the results obtained from this study, it can be concluded that the use of the make a match model has an increase in students' comprehension abilityKey words: Understanding, Make a Match Model, Learning Outcomes